Thai Universal Health Care Coverage scheme promotes the accessibility to cleft lip/palate treatment: the result of cleft care provision assessment using modified Geographic Information System - Chonnapasatid W. (2023)
Background: This study assessed the cleft lip/palate (CL/P) healthcare provision using data from the Thailand National Health Security Office from fiscal years 2012–2016. Methods: Four national databases of Thailand comprising 1) admitted patient visit, 2) non-admitted patient visit, 3) birth defects registry and 4) civil registration databases were analyzed. All duplicate records were removed by a matching process using national identity number and date of birth prior to data extraction. Modified Geographic Information System was also used to compare each provincial patients with CL/P of Thailand to the number of provincial live births with CL/P. Results: The results showed that the number of live births with CL/P during this period was 7,775 cases (1,555 cases/fiscal year). While the number of cases with CL/P registered under the Universal Health Care Coverage with hospital stay was 6,715 (86.37%), 927 cases (11.92%) visited hospitals without a stay, and the remaining 133 cases (1.71%) never visited any hospital. Modified Geographic Information System result showed that the provincial CL/P healthcare was relatively well-balanced with the provincial live births with CL/P (r = 0.92, p < 0.05). Moreover, provinces with CL/P tertiary care centers attracted more patients from the surrounding provinces. Conclusion: This study showed that the percentage of patients with CL/P receiving hospital treatment was 98. The Thai Universal Health Care Coverage scheme has promoted the accessibility to CL/P treatment. In order to achieve the best possible comprehensive cleft care coverage, periodical assessment and improvement of the function and accuracy of the national database registry are recommended.